The grotesque in selected modern Persian and post-war British short stories - Moghadam, Nahid Shahbazi (2013)
The grotesque enjoys a long history and a wide range of theoretical discussions which provide various, sometimes diverse, interpretations of this artistic and literary genre. While some scholars discuss the grotesque in association with related fields of study such as psychology or philosophy, some others basically focus on the grotesque itself. From a different perspective, the grotesque is also considered as a subject of study in terms of any or all the three levels of production; author (artistic mind), work (creation) and reader response (reception). The present study concentrates on the theories of the grotesque per se, and it is basically involved with work and partly with reception, considering that some elements of the grotesque are related to the effects it produces. This research discusses the grotesque as a focal image and mode of representation, based on a pattern developed from its recurrent elements. Accordingly, the recurrent features of the grotesque are drawn from the scholarship and are then classified and developed into hallmarks constituting the framework presented by this study. The grotesque, as a subcategory of Western aesthetics in art and literature, is also studied in this dissertation for its adaptability and extension to non-Western literature, namely short fiction. The study is thus devoted to a textual reading of selected Modern Persian as well as Post-war British short fiction. It is sought to trace the grotesque through its basic pattern in the interpretation of works from both literary traditions. In this regard, pairs of stories are thematically matched through motifs potentially associated with the grotesque. This is in line with the methodological approach to comparative studies, which requires a point of departure as the rationale for the comparison. Four sections in two discussion chapters are devoted to textual analysis of four pairs of stories. Textual analysis for each section initiates with a discussion on the common motif and is followed by close readings of both stories in the pair, which are read and interpreted in their depiction of the grotesque. A final section on each story pair concludes on the commonalities due to grotesque representations and elaborates on the variations of grotesque fiction as portrayed. This implies that the classification of grotesque fiction and its interrelatedness with the fantastic and caricature are also elaborated on. This study suggests that common misunderstandings and interpretive contradictions surrounding the meaning and the structure of the grotesque have most to do with its variations and interrelatedness, which can be best explicated in terms of its comprising a basic pattern with flexibility for its merger with other terms and modes.